MALAY CULTURE IN THE KINGDOM OF SINTANG - Susanto, Heru; Triani, Susan Neni; Qomariah, Qomariah (SEBASA Jurnal Pendidikan Bahasa dan Sastra, 2021)
This study aims to: 1) describe the Sintang Sintang Malay cultural social system; 2) The description of the language system includes the language used by the Sintang people in their daily interactions in order to communicate with each other; 3) A description of the knowledge system that can help the survival of the Sintang Malay community; 4) a description of the Sintang Malay cultural living equipment system in the Sintang Kingdom poem; 5) description of the Sintang Malay cultural livelihood system; 6) description of the Sintang Malay cultural religious system; 7) a description of the Sintang Malay cultural arts system. This study uses a descriptive method, with a qualitative research form. The source of data in this study comes from the verses of the Sintang Kingdom. The results of the study are as follows, the first data concerning the social system contains quotes about the stanzas regarding the aspects of deliberation to reach consensus, both in the inter-work environment, between royal members, and in a smaller environment, namely the nuclear family. used in syair. The third data is a knowledge system which is divided into knowledge of human nature, knowledge of nature, knowledge of objects. The fourth data is about living equipment which is divided into several aspects, namely transportation of ships, bidars, and canoes. The production is cerana, the clothing aspect is clothes, selawar, and songket cloth. There are traditional weapons, namely kris and cannons. The existence of a place to live or shelter, namely awnings, tents and mosquito nets, the existence of a container, namely the existence of a bamboo or lampstand as a place for lamps, as well as food and drink aspects, namely sherbet and juadah water. The sixth data, the religious system has aspects of marriage salvation, thanksgiving celebrations, worship, and the occult. The seventh data, which contains the art system on the sense of sight, the presence of Malay dance and theater and the sense of hearing, the presence of musical instruments typical of the Malay community.Keywords: Culture, Sintang Malay, Sintang Kingdom Poem